Emerging Innovations in Pharmaceutical Drug Delivery and Formulation Technologies: Current Advances, Clinical Relevance and Future Perspectives - Amar M. Raval; Fayeja M. Zankhwala; Pratiksha C Chandragirivar; Rakesh S A (Asian Journal of Pharmaceutical Research and Development, 2026)
Pharmaceutical sciences have undergone remarkable transformation over the past decade due to advances in formulation development, excipient engineering, nanotechnology, analytical techniques, digital healthcare, and regulatory sciences. The increasing prevalence of chronic diseases, antimicrobial resistance, patient-specific therapeutic requirements, and demand for improved healthcare outcomes has accelerated innovation in pharmaceutical technology. Traditional dosage forms often face limitations such as poor aqueous solubility, inadequate bioavailability, instability, limited permeability, and poor patient adherence. These limitations have encouraged the development of advanced oral delivery systems, transdermal formulations, nanotechnology-based carriers, and multifunctional excipient platforms. Recent pharmaceutical innovation has focused on improving therapeutic effectiveness while simplifying administration and enhancing patient convenience. Fast dissolving tablets, gastro-retentive systems, solid dispersions, microneedles, vesicular delivery systems, and nanocrystal formulations have demonstrated substantial clinical and industrial relevance. Simultaneously, advances in analytical method development and validation have improved product quality, regulatory compliance, and stability assessment. Artificial intelligence has emerged as a transformative tool in pharmaceutical research and healthcare practice, contributing to drug discovery, precision medicine, and digital pharmacovigilance. In parallel, growing attention to pharmacovigilance and materiovigilance has strengthened post-marketing safety monitoring and regulatory decision-making. This review comprehensively discusses recent innovations in pharmaceutical drug delivery and formulation technologies, including oral delivery systems, excipient engineering, transdermal technologies, nanotechnology, analytical science, digital transformation, safety monitoring, and future pharmaceutical trends. Emphasis is placed on clinical applicability, translational significance, and future opportunities in patient-centered pharmaceutical care.